Psicoterapia de crianças em instituição pública de saúde: novas perspectivas a partir do olhar da criança - Polli, Rodrigo Gabbi (2012)
Several issues pass through the mind of the therapist who ventures into the field of child psychotherapy, making them reflect and seek knowledge to guide their practice. This study aimed to investigate how children under psychological care in public health institution, in basic health institution, represent their therapy and their therapist. For this purpose, a qualitative study was carried out, using the draw and tell a story procedures. Eight children between five and twelve years old participated in this study. The children were asked to perform a sequence of three drawing-stories. The data analysis was performed using content analysis. The results are presented in the form of scientific papers. The first article focuses on the representation of the psychotherapy and the second on the representation of a psychotherapist. The results of the first study showed that children experienced their therapy as a place where they could play and talk about themselves. The emphasis given by the children to the ludic resources and to the conversations points out the importance of these therapeutic tools, since they enable children to communicate and work on their issues. Moreover, the treatment was experienced by the children as a place where changes happen in order to achieve therapeutic gains and improvements. The results of the second study suggest that children have a representation of a psychologist as someone who plays and talks with them. In order to make the therapeutic process happen, the ability of the professional to provide a reliable and supported environment was valued. In this place, the child feels safe to bring up their issues, highlighting the holding received during the treatment. The final considerations highlight the possibility of having services of quality in public health institutions, since psychotherapy has been experienced by children as the literature indicates, that is, regardless the place it happens and the people who take it.